2019
DOI: 10.1002/er.4755
|View full text |Cite
|
Sign up to set email alerts
|

A high proportion of new energy access–combined cooling, heating, and power system planning method

Abstract: Summary Distributed generation (DG) technologies are environmentally friendly and have low operating costs, and thus, distributed generators are widely used for the energy supplies of buildings. Solar energy used for on‐demand heating of buildings is also a mature technology that is environmentally friendly and inexpensive and has a short recycling life cycle. This paper proposes a high proportion of new energy access–combined cooling, heating, and power (HPNE‐CCHP) system composed of a distributed generator a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the meantime, it has also restrained renewable energy consumption, resulting in resource losses such as wind abandonment and abandonment of light. Currently, the lack of power ancillary service resources has become an urgent problem worldwide (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, it has also restrained renewable energy consumption, resulting in resource losses such as wind abandonment and abandonment of light. Currently, the lack of power ancillary service resources has become an urgent problem worldwide (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The NO X emissions of the system are calculated according to the emission factors of different pieces of equipment in the system. The sources of NO X emission and the corresponding emission factors are listed in Table 2 [60,61]. Moreover, the SO 2 emissions in an IES mainly come from the consumed coal.…”
Section: Type Of Subsystem Sequence Of Operation For Various Pieces O...mentioning
confidence: 99%
“…Performance of conventional compressed air energy storage (CAES) system has been compared with three combined heating-CAES systems. A novel solar-assisted integrated system comprised of combined cooling, heating, and power (CCHP) and distributed generator was analyzed by Zhang et al 37 The system was optimized using genetic algorithm-II taking life cycle cost and life cycle pollutant emissions into consideration. Results showed that high portion of new energy access-CCHP was more eco-friendly and economical as compared to the conventional CCHP system.…”
Section: Introductionmentioning
confidence: 99%